Efficient Retail Pricing in Electricity and Natural Gas Markets - Puller, Steven L; West, Jeremy (American Economic Review, 2013)
A long line of research investigates whether the retail prices of electricity and natural gas send proper signals about scarcity in order to induce efficient consumption. Historically, regulated utilities have not designed tariffs that set marginal prices equal to marginal costs. Currently, some jurisdictions are opening the retail sectors to competition via “retail choice.” These new regimes replace imperfect regulation with imperfect competition as the process by which retail tariffs are formed. We discuss the challenges in evaluating the efficiency of tariffs and present evidence of how pricing has changed in markets with retail choice.